An Ordinance for the Punishment of Offenses, § 39, DAYTON, LAWS AND GENERAL ORDINANCES 204, 214 (Law Passed 1842; Published 1855 Empire Steam Printing) (Dayton, Ohio). - (:unkn) unknown (General Publisher, 1842)
. If any person, or persons, shall fire any cannon, gun, or other firearms, within the bounds of the building lots, or cemetery ground in this city, or within one hundred yards of any public road, within this corporation, except by permission of council, and except in proper situations for firing salutes, or by command of a military officer in the performance of military duty, every person, so offending, on conviction thereof, shall pay a fine not exceeding ten dollars, and costs."
--
Keywords: DISCHARGE